Process for improving drying strength of ceramic body through layered material distribution and ceramic body

By arranging the thermosetting resin and the blank mixed reinforcement material on the bottom layer of the ceramic wet blank, the problem of insufficient strength of the marble tiles is solved, and the effect of efficiently improving the dry strength is achieved, while reducing production costs and environmental impacts.

CN119610342APending Publication Date: 2025-03-14QINGYUAN GANI CERAMICS CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510007516.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The prior art is difficult to improve the dry blank strength of marble ceramic tiles without increasing production costs and environmental impacts, especially when using raw ore shavings and reinforcers, which faces the problems of scarcity of resources, restrictions on environmental protection regulations and unstable product quality.

Method used

The layered fabric process is adopted, and the thermosetting resin is mixed with the blank as a reinforcement material, and evenly arranged on the bottom of the ceramic wet blank, and a three-dimensional network structure is formed during the drying process to improve the drying strength of the blank.

Benefits of technology

Through this process, the drying strength of the ceramic body is significantly improved, the amount of reinforcement material is used, the production cost is reduced, and the quality and environmental performance of the product are ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119610342A_ABST
    Figure CN119610342A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of architectural ceramics, and particularly relates to a process for improving the drying strength of a ceramic body through layered material distribution and the ceramic body. The process comprises the following steps: S1, carrying out ball-milling mixing on thermosetting resin and a blank to serve as a blank reinforcing material for later use; s2, the reinforcing material prepared in the step S1 is evenly arranged on one side of a blank of a to-be-pressed and formed body, the reinforcing material and the blank are pressed and formed together, a ceramic wet blank is obtained, and in the obtained ceramic wet blank, a reinforcing material layer is located at the bottom of the ceramic wet blank; and S3, drying the wet ceramic blank to obtain a dry blank. The thermosetting resin and the blank are mixed to prepare the reinforcing material, and a small amount of the reinforcing material is laid on the bottom layer of the blank in a layered material distribution mode, so that the side effect on the performance of the blank caused by ignition loss of the resin at high temperature is greatly reduced; the use cost of the reinforcing agent is greatly reduced; glass fibers can also be introduced to further improve the toughness and slow down the crack propagation after the green body is stressed, so that the overall strength of the green body is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of building ceramics, and in particular to a process for improving the drying strength of a ceramic body by layering materials and a ceramic body. Background Art

[0002] In the production process of ceramic tiles, marble tiles are widely welcomed by the market for their realistic natural marble texture and superior physical properties. In order to meet the demand for high texture and high stability in the production process, the dry blank strength of ceramic tiles has become an important technical indicator. Generally speaking, in order to perfectly use screen printing technology in the production process of marble tiles, the dry blank strength needs to reach ≥1.8MPa to meet production requirements and avoid cracking. The traditional method of improving the strength of dry blank mainly relies on the introduction of raw ore mud as raw material. The raw ore mud has a relatively rough particle structure and contains larger particles, which helps to form a good bond between particles during the molding process, thereby improving the strength of the green blank. In addition to the use of raw ore mud, the addition of reinforcing agent is also an effective method to improve the strength of dry blank. The reinforcing agent enhances the dry blank strength of ceramic tiles by improving the fluidity of the mud and increasing the density and uniformity of the blank.

[0003] However, the use of raw clay faces the problem of increasingly scarce resources, and its mining is subject to strict environmental regulations, which not only affects the stability of the supply chain, but also increases production costs. In addition, the organic matter contained in the raw clay may cause exhaust difficulties during the production process, thereby affecting the quality of the tiles, such as the production of defects such as black cores, which limits the increase in the production capacity of marble tiles. At this time, if the use of raw clay is reduced, the drying strength of the tiles will be greatly reduced, which will not meet the production process of marble tiles. Although the enhancer can improve the strength of the tile body, it also has some disadvantages. For example, the enhancer may affect the final color and texture of the tile, increase production costs, have a certain impact on the environment, and require precise control of the amount of addition to avoid instability in the performance of the tile. In addition, some organic enhancers show excellent properties in terms of strength, such as thermosetting resins. The network structure formed by them can greatly enhance the drying strength of the ceramic body. However, this kind of green body mixed with a large amount of raw materials has an extremely high burn-out rate after high-temperature sintering. The generation of a large number of pores causes the firing strength of the tile to drop sharply and the water absorption rate to increase greatly, thus failing to meet the subsequent use of the tile.

[0004] In this context, a new process for improving the dry strength of marble tiles was proposed, aiming to achieve high dry strength of tile bodies through innovative process preparation methods, while ensuring production efficiency and product quality, meeting the application of screen printing technology in the production process of marble tiles and the market demand for high-performance marble tiles. Summary of the invention

[0005] In order to solve the problem of low drying strength blanks breaking due to vibration when moving on the production line belt and the problem of blank defects caused by high pressure screen printing technology, the main purpose of the present invention is to provide a process for improving the drying strength of marble tiles after dry pressing and drying.

[0006] To achieve the above object, the technical solution adopted by the present invention is:

[0007] A process for improving the drying strength of a ceramic body by layering materials, comprising the following steps:

[0008] S1, mixing the thermosetting resin with the blank by ball milling and using it as a blank reinforcement material for standby use;

[0009] S2, evenly arranging the reinforcing material prepared in step S1 on one side of the green body to be pressed and formed together with the green body to obtain a ceramic green body, wherein the reinforcing material layer is located at the bottom of the ceramic green body,

[0010] S3, drying the ceramic wet blank obtained in step S2 to obtain a dry blank.

[0011] Furthermore, in step S1, the thermosetting resin includes but is not limited to phenolic resin.

[0012] Furthermore, in step S1, according to the mass ratio, the thermosetting resin: the blank = 1 to 10: 100. Preferably, according to the mass ratio, the thermosetting resin: the blank = 1 to 8: 100.

[0013] Furthermore, in step S2, the mass ratio of the blank to the reinforcing material is 100:10 to 20. In one preferred embodiment, the mass ratio of the blank to the reinforcing material is 100:13.2.

[0014] Furthermore, in step S3, the drying temperature is 150-200° C., and the drying time is 60-90 min.

[0015] Preferably, in step S1, the thermosetting resin, glass fiber and blank are mixed by ball milling and used as blank reinforcement material.

[0016] Furthermore, the specification of the glass fiber is 30-100 mesh.

[0017] Furthermore, in step S1, according to the mass ratio, thermosetting resin: glass fiber: blank = 1-10: 1-5: 100. In one preferred embodiment, thermosetting resin: glass fiber: blank = 5.27: 1: 100.

[0018] The blank mixed in the reinforcing material must be consistent with the blank used in the blank itself. In a preferred embodiment, the composition of the blank is SiO2: 69.7%, Al2O3: 20.30%, Fe2O3: 0.35%, TiO2: 0.03%, CaO: 0.32%, MgO2: 0.08%, K2O: 4.95%, Na2O: 1.68%, LOI: 2.63% in terms of mass percentage.

[0019] Another aspect of the present invention provides a ceramic body, comprising a green sheet and a reinforcing material layer disposed at the bottom of the green sheet, wherein the reinforcing material layer comprises green sheet and thermosetting resin, wherein the thermosetting resin includes but is not limited to phenolic resin.

[0020] Further preferably, the reinforcement material layer also includes glass fiber. In some embodiments, the specification of the glass fiber is 30-100 mesh.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] 1) The process of improving the drying strength of ceramic green bodies of the present invention uses a thermosetting resin and an original green body to mix and prepare a reinforcing material. During the heating process, on the one hand, the thermosetting resin undergoes an addition reaction and a polycondensation reaction to form a three-dimensional network structure with a large molecular weight. This structure enables the material to evenly disperse stress when subjected to external force, thereby improving the mechanical properties of the material. On the other hand, after the thermosetting resin is mixed in the green body, it has a certain fluidity and adhesiveness when heated at a certain temperature, and can fill the gaps between the material particles during the drying process, effectively connecting the green body particles, and further strengthening the strength of the green body after cooling.

[0023] 2) Furthermore, glass fiber can be introduced to improve the toughness of the reinforcing material and slow down the expansion of cracks after the blank is subjected to stress, thereby improving the overall strength of the blank.

[0024] 3) The present invention adopts a layered material laying process, and only a small amount of reinforcing material is arranged at the bottom of the brick. This design concept is intended to take into account that the brick needs to be transported for a long distance on the conveyor belt on the production line. The violent vibration of the conveyor belt will cause the bottom of the brick to be damaged first. Therefore, the improvement of the bottom strength will greatly reduce the occurrence of this situation, thereby further protecting the overall integrity of the dried body. On the other hand, laying only on the bottom also greatly reduces the amount of reinforcing material used, reducing the increase in cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 Schematic diagram of the process principle of an embodiment of the present invention. DETAILED DESCRIPTION

[0026] In order to more clearly illustrate the purpose and technical advantages of the present invention, the present invention is further described in conjunction with the following embodiments. Obviously, the embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, other embodiments obtained by ordinary technicians in this field without making creative work are all within the scope of protection of the present invention. In addition, the technical solutions between the various embodiments can be combined with each other, but they must be based on the ability of ordinary technicians in this field to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention.

[0027] The bottom of the green body mentioned in the embodiment of the present invention refers to the side of the green body that contacts the conveyor belt of the brick production line.

[0028] The phenolic resin used in the following examples has a specification of 200 mesh and a molecular weight of 1800-2500.

[0029] The specification of glass fiber is 30-100 mesh.

[0030] The composition of the blank is: SiO2: 69.7%, Al2O3: 20.30%, Fe2O3: 0.35%, TiO2: 0.03%, CaO: 0.32%, MgO2: 0.08%, K2O: 4.95%, Na2O: 1.68%, LOI: 2.63%

[0031] Example 1

[0032] refer to Figure 1 , a process for improving the drying strength of a ceramic body by layering materials, comprising the following steps:

[0033] S1, 30g of the blank and 0.3g of phenolic resin were ball-milled and mixed for 20min to obtain a blank reinforcement material for standby use;

[0034] S2, placing 26.5 g of the blank in a mold, taking 3.5 g of the reinforcing material obtained in step S1, evenly arranging it on the upper layer of the blank, and then pressing them together into a wet blank block of about 80*40*4 mm, wherein the reinforcing material layer is located at the bottom of the wet blank block;

[0035] S3. The wet green body obtained in step S2 is placed in an oven and dried at 150° C. for 70 min to obtain a dry green body.

[0036] The obtained green body comprises a green material layer and a reinforcing material layer located at the bottom of the green material layer, and the reinforcing material layer comprises green material and phenolic resin.

[0037] Example 2

[0038] refer to Figure 1 , a process for improving the drying strength of a ceramic body by layering materials, comprising the following steps:

[0039] S1, 30g of blank, 0.3g of phenolic resin and 0.3g of glass fiber were ball-milled and mixed for 20min to obtain a blank reinforcement material for standby use;

[0040] S2, placing 26.5 g of the blank in a mold, taking 3.5 g of the reinforcing material obtained in step S1, evenly arranging it on the upper layer of the blank, and then pressing them together into a wet blank block of about 80*40*4 mm, wherein the reinforcing material layer is located at the bottom of the wet blank block;

[0041] S3. The wet green body obtained in step S2 is placed in an oven and dried at 150° C. for 70 min to obtain a dry green body.

[0042] The obtained green body comprises a green body layer and a reinforcing material layer located at the bottom of the green body layer, and the reinforcing material layer comprises green body, phenolic resin and glass fiber.

[0043] Example 3

[0044] refer to Figure 1 , a process for improving the drying strength of a ceramic body by layering materials, comprising the following steps:

[0045] S1, 30g of blank, 0.98g of phenolic resin and 0.3g of glass fiber were ball-milled and mixed for 20min to obtain a blank reinforcement material for standby use;

[0046] S2, placing 26.5 g of the blank in a mold, taking 3.5 g of the reinforcing material obtained in step S1, evenly arranging it on the upper layer of the blank, and then pressing them together into a wet blank block of about 80*40*4 mm, wherein the reinforcing material layer is located at the bottom of the wet blank block;

[0047] S3. The wet green body obtained in step S2 is placed in an oven and dried at 150° C. for 70 min to obtain a dry green body.

[0048] The obtained green body comprises a green body layer and a reinforcing material layer located at the bottom of the green body layer, and the reinforcing material layer comprises green body, phenolic resin and glass fiber.

[0049] Example 4

[0050] refer to Figure 1 , a process for improving the drying strength of a ceramic body by layering materials, comprising the following steps:

[0051] S1, 30g of blank, 1.58g of phenolic resin and 0.3g of glass fiber were ball-milled and mixed for 20min to obtain a blank reinforcement material for standby use;

[0052] S2, placing 26.5 g of the blank in a mold, taking 3.5 g of the reinforcing material obtained in step S1, evenly arranging it on the upper layer of the blank, and then pressing them together into a wet blank block of about 80*40*4 mm, wherein the reinforcing material layer is located at the bottom of the wet blank block;

[0053] S3. The wet green body obtained in step S2 is placed in an oven and dried at 150° C. for 70 min to obtain a dry green body.

[0054] The obtained green body comprises a green body layer and a reinforcing material layer located at the bottom of the green body layer, and the reinforcing material layer comprises green body, phenolic resin and glass fiber.

[0055] Example 5

[0056] refer to Figure 1 , a process for improving the drying strength of a ceramic body by layering materials, comprising the following steps:

[0057] S1, 30g of blank, 2.26g of phenolic resin and 0.3g of glass fiber were ball-milled and mixed for 20min to obtain a blank reinforcement material for standby use;

[0058] S2, placing 26.5 g of the blank in a mold, taking 3.5 g of the reinforcing material obtained in step S1, evenly arranging it on the upper layer of the blank, and then pressing them together into a wet blank block of about 80*40*4 mm, wherein the reinforcing material layer is located at the bottom of the wet blank block;

[0059] S3. The wet green body obtained in step S2 is placed in an oven and dried at 150° C. for 70 min to obtain a dry green body.

[0060] The obtained green body comprises a green body layer and a reinforcing material layer located at the bottom of the green body layer, and the reinforcing material layer comprises green body, phenolic resin and glass fiber.

[0061] Comparative Example 1

[0062] A process for preparing a ceramic body comprises the following steps:

[0063] S1. Place 30g of the original blank in a mold and press it into a block of about 80*40*4mm;

[0064] S2. The wet green body obtained in step S2 is placed in an oven and dried at 150° C. for 70 min to obtain a dry green body.

[0065] Comparative Example 2

[0066] A process for preparing a ceramic body comprises the following steps:

[0067] S1. Place 30 g of the reinforcing material in Example 4 into a mold and press it into a block of about 80*40*4 mm;

[0068] S2. The wet green body obtained in step S2 is placed in an oven and dried at 150° C. for 70 min to obtain a dry green body.

[0069] The dried green bodies obtained in the examples and comparative examples were tested for drying strength and sintering strength using a ceramic flexural tester. The results are shown in Table 1.

[0070] Table 1 Strength test results

[0071] sample Dry billet strength (MPa) Firing strength (MPa) Example 1 1.12 / Example 2 1.33 / Example 3 1.71 / Example 4 2.51 18.55 Example 5 2.31 / Comparative Example 1 0.64 19.67 Comparative Example 2 4.95 8.61

[0072] This solution uses a layered material laying process method to evenly lay less reinforcement material on the bottom of the tile to improve the dry strength of the green body. Specifically, as shown in Table 1, the green body of Comparative Example 1 has not been laid with a bottom layer of additive material, and its strength is only 0.64MPa, which is far from meeting the transportation requirements of the conveyor belt on the production line and screen printing. After laying a reinforcement layer at the bottom of the tile with the original green body as the matrix, thermosetting phenolic resin as the main reinforcing agent, and glass fiber as the auxiliary reinforcing material, the strength of the green body after drying is significantly improved. Specifically, from Examples 1 and 2, after adding a small amount of glass fiber to the reinforcement layer, its strength is increased by 18.8%, indicating that glass fiber can play a certain role in improving strength as an auxiliary reinforcement material in the reinforcement layer.

[0073] The data from Examples 2-5 show that as the content of phenolic resin increases, the strength of the green body after drying continues to increase, increasing by 107.8%, 167.2%, 292.2%, and 260.9% respectively. It can be seen that after laying the reinforcing material at the bottom, the overall dry strength of the green body is greatly improved, indicating that the adhesiveness of the phenolic resin and the network structure formed bring a greater reinforcement effect to the brick. However, when an excessive amount of phenolic resin is added, as shown in Example 5, the strength of the green body after drying is reduced by about 8% compared with Example 4. This is because the phenolic resin has a certain brittleness. If it accounts for too large a proportion in the reinforcement layer, this disadvantage of the phenolic resin begins to become significant.

[0074] In addition, the laying process of the reinforcing material also affects the performance of the brick blank. As shown in Comparative Example 2, after the reinforcing material is pressed and formed as a whole as the blank, the dry strength of the blank is significantly improved. However, the phenolic resin is manifested in the whole blank due to its own brittleness, and the burning loss of the phenolic resin causes the firing strength of the tile to drop sharply, which obviously does not meet the normal use of the tile; in addition, an excessively high proportion of phenolic resin will also affect the shrinkage of the blank at high temperature, causing the brick blank to deform. Therefore, only by laying the reinforcing material in layers in the present application scheme and arranging a small amount of reinforcing material at the bottom of the brick blank can the defective characteristics of the phenolic resin be minimized without affecting its adhesiveness and network structure.

[0075] In summary, the scheme of the present invention, by selecting the original blank as the matrix, the thermosetting phenolic resin as the main reinforcing agent, and further adding glass fiber as an auxiliary reinforcing material, is mixed to form a blank reinforcement material, and then combined with the layered laying process, the reinforcement material is laid on the bottom of the brick, which can give play to the adhesiveness and network structure of the phenolic resin, and appropriately avoid the brittleness of the material itself, thereby improving the overall quality of the blank. In addition, the matrix selection of the bottom reinforcement material in the present invention is subject to the principle of being consistent with the main body of the blank. Such a design ensures that the physical and chemical properties between the main body and the reinforcement remain similar during the sintering process, thereby not causing defects after the ceramic tile is fired. In short, the process of improving the dry strength of the ceramic blank by layered cloth in this application has a strong reinforcing effect, which satisfies the stable transportation process of the blank on the production line.

[0076] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0077] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A process for improving the drying strength of a ceramic body by layering materials, characterized in that: The steps include: S1, mixing the thermosetting resin with the blank by ball milling and using it as a blank reinforcement material for standby use; S2, evenly arranging the reinforcing material prepared in step S1 on one side of the green body to be pressed and formed together with the green body to obtain a ceramic green body, wherein the reinforcing material layer is located at the bottom of the ceramic green body; S3, drying the wet ceramic blank obtained in step S2 to obtain a dry ceramic blank.

2. The process for improving the drying strength of a ceramic body according to claim 1, characterized in that: In step S1, the thermosetting resin is a phenolic resin.

3. The process for improving the drying strength of a ceramic body according to claim 1, characterized in that: In step S2, the green body is pressed to a size of 30 to 120 g.

4. The process for improving the drying strength of a ceramic body according to claim 1, characterized in that: In step S2, the mass ratio of the blank to the reinforcing material is 100:10-20.

5. The process for improving the drying strength of a ceramic body according to claim 1, characterized in that: In step S3, the drying temperature is 150-200° C., and the drying time is 60-90 minutes.

6. The process for improving the dry strength of a ceramic body according to any one of claims 1 to 5, characterized in that: In the step S1, the thermosetting resin, the glass fiber and the blank are ball-milled and mixed to be used as the blank reinforcement material.

7. The process for improving the dry strength of a ceramic body according to claim 6, characterized in that: In step S1, the mass ratio of thermosetting resin: glass fiber: blank is 1-10:1-5:

100.

8. The process for improving the drying strength of a ceramic body according to claim 6, characterized in that: The specification of the glass fiber is 30-100 meshes.

9. A ceramic body, characterized in that: The invention comprises a blank layer and a reinforcing material layer arranged at the bottom of the blank layer, wherein the reinforcing material layer comprises the blank and a thermosetting resin.

10. The ceramic body according to claim 9, characterized in that: The reinforcement material layer also includes glass fibers.